Analisis Pengaruh Price Discount, Hedonic Shopping Motivation Terhadap Impulse Buying Pada Konsumen Shopee-Id - Elly Ayu Lestari; Heri Prabowo; Rauly Sijabat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is motivated by the community that is currently dependent on the facilities provided by the internet , with the facilities provided by the internet the community is able to meet everything The desired needs, one of which is online shopping transactions.The purpose of this study was to determine whether there is a significant influence between price discounts and hedonic shopping motivation on impulse purchases in consumers Shoppe_id students FEB PGRI University Semarang class of 2017 /2019. In conducting this research, researchers are guided by previous studies and the research method used is quantitative research with the determination of data sources using non-probability sampling and accidental samling, for the validity of the data researchers took from the Student Administration Bureau which had been processed by researchers using SPSS 26. The results of the analysis in this study stated that the price discount (X1) sig value of 0.035 which means that the price discount have a significant effect on impulse buying (Y), while for hedonic shopping motivation (X2) shows a sig value of 0.000 which means motivasi hedonic shopping has a significant influence on impulse buying (Y).